Dlouhodobá mechanická srdeční podpora v terapii chronického srdečního selhání - reálná praxe - Pavlů, Luděk; Vícha, Marek; Jelínek, Libor; Táborský, Miloš; Petřková, Jana (Vnitrni lekarstvi, 2021)
Thanks to developments in pharmacological and non-pharmacological treatment of heart failure over the last half century, there has been improved quality of life and reduced mortality and morbidity. Despite these advances, the prognosis of advanced heart failure remains poor and the number of patients with terminal heart failure is currently increasing. In the general medical community, knowledge of pharmacological and device therapy with implantable cardioverter-defibrillator or resynchronization therapy is prevalent. However, only a limited number of professionals, mostly in tertiary centres, have personal experience with the use of long-term mechanical circulatory support (MCS) in patients with advanced heart failure after the above conventional therapeutic options have been exhausted. The purpose of this communication is, therefore, to provide the general medical community with basic information about benefits, limitations and referral strategies for MCS.
Keywords: advanced heart failure; Defibrillators, Implantable; Heart Failure; lidé; type 2 diabetes; srdeční selhání; chronická nemoc; Humans; kvalita života; defibrilátory implantabilní; long‑term mechanical circulatory support; therapy; Heart-Assist Devices; podpůrné srdeční systémy; Chronic Disease; Quality of Life